2021
DOI: 10.3390/genes12070974
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Genomic Profiles of Atypical Fibroxanthoma and Pleomorphic Dermal Sarcoma Identify Overlapping Signatures with a High Mutational Burden

Abstract: Atypical fibroxanthoma (AFX) and pleomorphic dermal sarcoma (PDS) are rare tumors developing in chronically sun-exposed skin. Clinicopathological features are similar, but they differ in prognosis, while PDS has a more aggressive course with a higher risk for local recurrence and metastases. In current clinical practice, they are diagnosed by exclusion using immunohistochemistry. Thus, stringent diagnostic criteria and correct differentiation are critical in management and treatment for optimal outcomes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(53 reference statements)
4
6
1
2
Order By: Relevance
“…These are thought to be ultraviolet‐induced and are consistent with the variant class (C>T/G>A) most frequently seen in our cases in agreement with tumors arising in chronically sun‐damaged skin. Similar findings have been observed in the majority of AFX and PDS cases subjected to molecular analyses to date 21–25 . Finally, ccPDS and ccAFX also showed no significant MSI, in accordance with a previous report 25 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These are thought to be ultraviolet‐induced and are consistent with the variant class (C>T/G>A) most frequently seen in our cases in agreement with tumors arising in chronically sun‐damaged skin. Similar findings have been observed in the majority of AFX and PDS cases subjected to molecular analyses to date 21–25 . Finally, ccPDS and ccAFX also showed no significant MSI, in accordance with a previous report 25 …”
Section: Discussionsupporting
confidence: 91%
“…However, some differences in genomic alterations were seen between the ccAFX and ccPDS cases. In contrast to the literature, TERT promoter and NOTCH2 mutations, present in the ccAFX but not in the ccPDS case, have previously been shown to occur in the majority of PDS cases 24,25 . In addition, mutations of the APC gene, observed in the ccPDS case only, were reported in 49% of PDS and 42% of AFX cases 25 .…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Recent clinical studies have identified tumor mutation burden (TMB) as an indicator for predicting response to immunotherapy ( Zhang W. et al, 2021 ). High TMB have better response to PD-1/PD-L1 therapy across diverse tumor entities ( Ak et al, 2021 ). Therefore, analyzing the relationship between glycolysis-related ceRNA networks, tumor-infiltrating immunity, TMB and drug sensitivity is critical to explain the potential molecular mechanisms implicated in the development of PAAD, and identify promising biomarkers and novel therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%